Sports therapy services (Handbook of sports medicine and science, 2012)
Handbook of Sports Therapy Services: Organization and Operations is a practical guide, appropriate for each member of the multi-disciplinary "Sports Therapy" team, to establishing and effectively delivering the diverse therapy services required for athletes at international, national, and regional sporting events.